2021
DOI: 10.3390/polym13213687
|View full text |Cite
|
Sign up to set email alerts
|

Extraction of Cyclic Oligomer and Their Influence on Polyester Dyeing in a Silicone Waterless Dyeing System

Abstract: As a promising new dyeing process without using water, the non-aqueous medium dyeing of polyester has attracted people’s attention and some progress has been made in related research. However, the oligomers of polyester fiber can affect the dyeing of polyester during the use of a silicone waterless dyeing system. Based on this point, the oligomer problem in the silicone waterless dyeing system was investigated. The oligomers of some different types of polyester were extracted by solvent extraction. A treatment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
(39 reference statements)
0
3
0
Order By: Relevance
“…The four diffraction peaks appeared near 14.7°, 16.5°, 22.7°, and 34.3°, resulted from the diffraction of (101), (101true¯), (002), and (040) crystal planes of cotton cellulose, respectively. The diffraction peak positions of the fabrics before and after dyeing did not change, indicating that mordant dyeing, CA + SUA crosslinked dyeing, and CPC/CA + SUA crosslinked dyeing mostly occurred in the non‐crystalline region of the cotton fabric and had little effect on the crystal structure of the cotton fabric 20 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The four diffraction peaks appeared near 14.7°, 16.5°, 22.7°, and 34.3°, resulted from the diffraction of (101), (101true¯), (002), and (040) crystal planes of cotton cellulose, respectively. The diffraction peak positions of the fabrics before and after dyeing did not change, indicating that mordant dyeing, CA + SUA crosslinked dyeing, and CPC/CA + SUA crosslinked dyeing mostly occurred in the non‐crystalline region of the cotton fabric and had little effect on the crystal structure of the cotton fabric 20 …”
Section: Resultsmentioning
confidence: 99%
“…The diffraction peak positions of the fabrics before and after dyeing did not change, indicating that mordant dyeing, CA + SUA crosslinked dyeing, and CPC/CA + SUA crosslinked dyeing mostly occurred in the non-crystalline region of the cotton fabric and had little effect on the crystal structure of the cotton fabric. 20 Table 2 demonstrates that the crystallinity of the three dyed cotton fabrics had little difference from that of raw cotton (65.06%). It was further shown that the dyeing behaviour mainly existed in the amorphous region of cotton fibre, which basically retained the original crystal shape of the original cotton.…”
Section: Xrd Analysismentioning
confidence: 98%
“…Unfortunately, to date, there are very few dyeing technologies for disperse dyes available in practice with the applicability of a waterless dyeing system, although polyester fabrics are dyed using an environmentally friendly method [ 29 , 30 , 31 , 32 ]. Therefore, the key to waterless dyeing technology is the dyeing medium in the dyeing process [ 33 ].…”
Section: Introductionmentioning
confidence: 99%